Pola Penerapan FRAGGLE dalam Produksi dan Pelatihan Produksi Boardgame sebagai Strategi Peningkatan Wisata Edukasi di Sanan - Muhammad Syifa'ul Qolbi; Mohamad Firzon Ainur Roziqin; Alby Aruna; Abdul Rahman Prasetyo; Eka Putri Surya; Adinda Marcelliantika; Ginanjar Atma Wijaya (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The application of the FRAGGLE model in boardgame production and production training as a strategy to enhance educational tourism in Sanan aims to integrate education and entertainment through boardgame media. This program utilizes the FRAGGLE model to develop educational and engaging boardgames while involving production training for the local community. Methods include boardgame design and development, technical production training, and effectiveness evaluation through user feedback. Results show significant improvement in production skills and visitor interest in boardgame-based educational tourism. The implementation of this strategy is expected to support the development of innovative educational tourism and empower the local community in Sanan.